2013
DOI: 10.4172/2161-0932.1000163
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and the Urinary Bladder

Abstract: The presence of the Endocannabinoid System (ECS) in the urinary bladder has led to speculation that endocannabinoid-signalling is involved in the signal transduction pathways regulating bladder relaxation and may be involved in pathophysiological processes of the bladder. On the basis of this evidence, it was postulated that the binding of endocannabinoids to the cannabinoid receptors (CB 1 and CB 2 ) may result in relaxation of the urinary bladder during the filling phase. Dysregulation of the ECS in human bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…The latter ones were also identified in detrusor cholinergic neurons and sensory suburothelial nerves expressing TRPV 1 and the calcitonin gene-associated peptide (CGRP) [45,55]. Furthermore, functional studies conducted by Bakali et al (2013) [48] showed that CB 2 receptors exerted both pre-and post-synaptic inhibitory effects on the contraction of the rat bladder, while CB 2 receptors exclusively act post-synaptically [49]. Stimulating both CB 1 andCB 2 receptors inhibits adenylyl cyclase from generating the cyclic-adenosine monophosphate (cAMP) by interaction with the α-subunit of the G protein of the G i/o family [56].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The latter ones were also identified in detrusor cholinergic neurons and sensory suburothelial nerves expressing TRPV 1 and the calcitonin gene-associated peptide (CGRP) [45,55]. Furthermore, functional studies conducted by Bakali et al (2013) [48] showed that CB 2 receptors exerted both pre-and post-synaptic inhibitory effects on the contraction of the rat bladder, while CB 2 receptors exclusively act post-synaptically [49]. Stimulating both CB 1 andCB 2 receptors inhibits adenylyl cyclase from generating the cyclic-adenosine monophosphate (cAMP) by interaction with the α-subunit of the G protein of the G i/o family [56].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, functional studies conducted by Bakali et al (2013) [48] showed that CB 2 receptors exerted both pre-and post-synaptic inhibitory effects on the contraction of the rat bladder, while CB 2 receptors exclusively act post-synaptically [49]. Stimulating both CB 1 andCB 2 receptors inhibits adenylyl cyclase from generating the cyclic-adenosine monophosphate (cAMP) by interaction with the α-subunit of the G protein of the G i/o family [56]. In turn, the orphan metabotropic GPR55 receptors (sometimes called CB 3 receptors) [57], among others, are also localized in the bladder [58], mainly in the urothelium [59].…”
Section: Introductionmentioning
confidence: 99%